2011
DOI: 10.1128/jvi.01838-10
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Friend Virus Replication and Disease in Apobec3 -Deficient Mice Expressing Functional B-Cell-Activating Factor Receptor

Abstract: Rfv3 is an autosomal dominant gene that influences the recovery of resistant mice from Friend retrovirus (FV) infection by limiting viremia and promoting a more potent neutralizing antibody response. We previously reported that Rfv3 is encoded by Apobec3 , an innate retrovirus restriction factor. However, it was recently suggested that the Rfv 3 susceptible phenotype of high viremia at 28 days postinfection (dpi) was more domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 48 publications
0
52
0
Order By: Relevance
“…F-MuLV RNA copy numbers in the plasma were measured by quantitative PCR (22, 31). RNA extracted from 5 μl of plasma was added to 1× One-Step Taqman Reverse Transcriptase-PCR reaction mixture (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…F-MuLV RNA copy numbers in the plasma were measured by quantitative PCR (22, 31). RNA extracted from 5 μl of plasma was added to 1× One-Step Taqman Reverse Transcriptase-PCR reaction mixture (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last five decades, numerous genetic factors that influence FV resistance and susceptibility have been identified (14). These genes include Fv1 , which mediates a capsid-dependent post-entry block (16); Fv2 , a dominant susceptibility gene that dictates splenomegaly induction (17); H-2 , the murine MHC which controls adaptive immune responses (18, 19); and Apobec3/Rfv3 , which influences recovery from viremia by promoting a stronger neutralizing antibody response (20-22). …”
Section: Introductionmentioning
confidence: 99%
“…We showed that deletion of B6 mA3 in (B6 ϫ A.BY)F 1 mice resulted in weaker NAb responses and abrogated recovery from viremia and disease by 28 days postinfection (dpi) (14,17). Removal of B6 mA3 in a pure B6 genetic background also resulted in weaker NAb responses (14,15).…”
mentioning
confidence: 93%
“…Athymic nude (Ncr-nu/nu) mice were obtained from the National Cancer Institute (NCI). C57BL/6J Apobec3 knockout (B6 Apobec3 Ϫ/Ϫ ) mice were generated previously (50). This animal study has been approved by the Institutional Animal Care and Use Committee at the University of Colorado [approval number 93913(12)1E].…”
Section: Methodsmentioning
confidence: 99%